Ryszard Kapuściński : biography of a writer - Nowacka, Beata; Ziątek, Zygmunt (McGill-Queen's University Press, 2023)
"An award-winning writer and a candidate for the Nobel Prize for Literature, Ryszard Kapuściński (1932-2007) was a celebrated Polish journalist and author. Praised for the lengths to which he would go to get a story, Kapuściński gained an extraordinary knowledge of the major global events of the second half of the twentieth century and shared it with his diverse audience. The first posthumous monograph on the writer's life and work, Ryszard Kapuściński confronts the mixed reception of Kapuściński's tendency to merge the conventions of reportage with the artistry of literature. Beata Nowacka and Zygmunt Ziątek discuss the writer's accounts of the decolonization of Africa and his work in Asia and South America between 1956 and 1981, a period during which Kapuściński reported on twenty-seven revolutions and coups. They argue that the journalistic tradition is not in conflict with Kapuściński's meditations on the deep meanings of these events, and that his first-person involvement in his text was not an indulgence detracting from his journalistic adventures but a well-thought-out conception of eyewitness testimony, developing the moral and philosophical message of the stories. Exploring the whole of Kapuściński's achievements, Nowacka and Ziątek identify a constant tension between a strictly journalistic position and what in Poland is called literary reportage, located on the border between journalism and artistic prose. Kapuściński's desire and dedication to make more of journalistic writing is the driving force behind the excellence and readability that have made his legendary books so controversial - and so widely celebrated."--